Das Testament als eine Textsorte. Eine linguistische Analyse des Testaments des galizischen Adligen Herman de Brunicki aus dem Jahre 1835 - Czachur, Waldemar; Zimmer, Agnieszka (Studia Germanica Posnaniensia, 2019)
The aim of the article is to show the specific characteristics of the Galician legal language in the first half of the 19th century. The article analyses the 1835 will of Baron Herman de Brunicki. First, the pattern of the will, its structure and function are examined. Further on, the author focuses on the graphematic, lexical and syntactic levels of the will.